2014
DOI: 10.1016/j.jmgm.2014.10.008
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-generational pharmacophore modeling for ligands to the cholane steroid-recognition site in the β1 modulatory subunit of the BKCa channel

Abstract: Large conductance, voltage- and Ca2+-gated K+ (BKCa) channels play a critical role in smooth muscle contractility and thus represent an emerging therapeutic target for drug development to treat vascular disease, gastrointestinal, bladder and uterine disorders. Several compounds are known to target the ubiquitously expressed BKCa channel-forming α subunit. In contrast, just a few are known to target the BKCa modulatory β1 subunit, which is highly expressed in smooth muscle and scarce in most other tissues. Lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, vascular SM BK channel activators are effective vasodilators, as reviewed in [93] while genetic ablation of the BK β1 subunit (e.g., in the KCNMB −/− mouse) is associated with increased myogenic tone [18]. Finally, β1 subunits embolden BK channels with distinct pharmacology, including channel activation by 17β-estradiol [180], micromolar levels of hydrophobic cholanes and their nonsteroidal analogs [22,23,29,132], leukotriene B4 [24], dehydrosoyasaponin-I [131], hydroclorothiazide [127], equol [203], tungstate [57], increased sensitivity to PIP 2 [179] and DHA [74,75], and ethanol-induced reduction of channel activity at low μM Ca 2+ ic [94,95]. The role of SM BK channels as pharmaco-therapeutic targets has been recently reviewed elsewhere [93,219].…”
Section: Basic Phenotype Of the Vascular Smooth Muscle Bk Channel Andmentioning
confidence: 99%
“…Therefore, vascular SM BK channel activators are effective vasodilators, as reviewed in [93] while genetic ablation of the BK β1 subunit (e.g., in the KCNMB −/− mouse) is associated with increased myogenic tone [18]. Finally, β1 subunits embolden BK channels with distinct pharmacology, including channel activation by 17β-estradiol [180], micromolar levels of hydrophobic cholanes and their nonsteroidal analogs [22,23,29,132], leukotriene B4 [24], dehydrosoyasaponin-I [131], hydroclorothiazide [127], equol [203], tungstate [57], increased sensitivity to PIP 2 [179] and DHA [74,75], and ethanol-induced reduction of channel activity at low μM Ca 2+ ic [94,95]. The role of SM BK channels as pharmaco-therapeutic targets has been recently reviewed elsewhere [93,219].…”
Section: Basic Phenotype Of the Vascular Smooth Muscle Bk Channel Andmentioning
confidence: 99%
“…ligands such as bile acids (Bukiya et al, 2011;Dopico et al, 2002) and the synthetic compound termed "HENA" (Bukiya et al, 2013). Indeed, celastrol satisfies major pharmacophore criteria for β 1 -containing BK channels (McMillan et al, 2014). Overall, celastrol maximal vasodilation ranges from 8-12% increase over pre-drug values, when we consider all systems here studied: de-endothelialized and intact isolated MCA segments, and cranial window MCA measurements in live rats.…”
Section: Discussionmentioning
confidence: 95%
“…Celastrol also exerts neuroprotection, which has been linked to its antioxidant and anti-inflammatory activities (Allison et al, 2001;Cleren et al, 2005;Kiaei et al, 2005;Paris et al, 2010). Remarkably, our group has identified that celastrol fits pharmacophore criteria for activation of BKs that include regulatory subunits abundant in cerebrovascular SM, and has further demonstrated that ex-vivo exposure of these recombinant heteromeric BKs in a heterologous expression system could be activated by celastrol (McMillan et al, 2014). The aim of this study is to determine whether 1) celastrol dilates cerebral arteries both ex-vivo and in-vivo; 2) this action requires the vascular endothelium or, rather, involves SM targets; 3) celastrol-induced cerebral dilation specifically involves BKs; 4) celastrol is able to counteract cerebral artery constriction evoked by ethanol concentrations found in blood during binge drinking.…”
Section: Introductionmentioning
confidence: 93%
“…4, 5 and 6) and BK β1 mRNA levels (Fig. 7) when compared to those of BA or CA, 2) rat MCA is a widely used experimental model to address human cerebrovascular pathophysiology and pharmacology [3,26,33,88], and 3) we conducted all our previous studies with smooth muscle BK β1-targeting vasodilators (LCA itself, other cholanes, LTB4 and HENA) using rat MCA [1517,19,63,74]. BK β1 protein overexpression was confirmed by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%